Multicultural Education in Indonesia: The Perspective of Islamic Educational Philosophy - Evi Verliantika; Isna Harisa; Ata Zamzami; Amirul Sodik; Ahmad Adib Rifai; Kalimatus Saroh; Joko Suprianto; Isti Mukhayanah; Rahmad Andi Sugiharto; Pita Andri Yani (Bulletin of Science Education, 2021)
Multicultural education in Indonesia plays a strategic role in managing the nation's rich diversity of cultures, ethnicities, religions, and languages. The perspective of Islamic educational philosophy provides a normative and ethical foundation to foster harmony amid differences. This study views multicultural education as an effort to cultivate awareness and tolerance through the appreciation of pluralistic values that align with Islamic principles such as justice, equality, and respect for human rights. Islamic educational philosophy emphasizes the centrality of tauhid (the oneness of God) as the basis for shaping inclusive character that honors diversity. Through this approach, multicultural education aims not only to develop students’ intellectual competencies but also to nurture their moral and ethical sensibilities for peaceful coexistence in a plural society. This study recommends the integration of multicultural and Islamic values into the educational curriculum to produce a generation that is tolerant, socially just, and capable of preserving diversity as a national asset. Keywords:  Multicultural Education, Educational Philosophy, Intellectual Competencies